2015
DOI: 10.1007/s13197-015-1938-5
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and functional properties of biodegradable pellets developed from various agro-industrial wastes using extrusion technology

Abstract: Different agro-industrial wastes were mixed with different plasticizers and extruded to form the pellets to be used further for development of biodegradable molded pots. Bulk density and macro-porosity are the important engineering properties used to determine the functional characteristics of the biodegradable pellets viz., expansion volume, water solubility, product colour, flowability and compactness. Significant differences in the functional properties of pellets with varying bulk densities (loose and tapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…According to Rosentrater [13], Maillard reactions and protein denaturing play main roles in colour alterations during the cooking process resulting from high temperatures. It was also observed that the color (∆E) value of samples containing CNSL as plasticizer were greater than samples containing glycerol as plasticizer which is due to the inherent dark color of the cashew nut shell liquid [7], resulting in maximum absorption of the light. In case of sheets, a significant increase in colour (∆E) was observed during pressing (hydraulic press) which may be due to higher temperature during processing as compared to that of pellets during extrusion.…”
Section: Color Of Pellets and Sheetsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Rosentrater [13], Maillard reactions and protein denaturing play main roles in colour alterations during the cooking process resulting from high temperatures. It was also observed that the color (∆E) value of samples containing CNSL as plasticizer were greater than samples containing glycerol as plasticizer which is due to the inherent dark color of the cashew nut shell liquid [7], resulting in maximum absorption of the light. In case of sheets, a significant increase in colour (∆E) was observed during pressing (hydraulic press) which may be due to higher temperature during processing as compared to that of pellets during extrusion.…”
Section: Color Of Pellets and Sheetsmentioning
confidence: 99%
“…The increased hardness may be attributed to the greater binding effect of CNSL as compared to glycerol. Moreover, the increased hardness measured by texture analyser is due to more resistance to compression [7]. Plasticizers are important to maintain dimensional stability, hardness and flexibility of protein-based polymer due to its high boiling temperature [9].…”
Section: Density and Hardness Of Pellets And Sheetsmentioning
confidence: 99%
See 2 more Smart Citations
“…It represents a sizeable and functional component to reinforce materials for biocomposites (Jan et al . ). Biopolymers generally present poor mechanical properties; hence, plasticizers are added to provide the necessary workability (Vieira et al .…”
Section: Introductionmentioning
confidence: 97%